1995
DOI: 10.1016/0735-1097(95)00254-2
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial infarction in young adults: Angiographic characterization, risk factors and prognosis (coronary artery surgery study registry)

Abstract: Young patients with a myocardial infarction have a favorable prognosis compared with that in older patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

49
347
7
32

Year Published

1997
1997
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 431 publications
(435 citation statements)
references
References 40 publications
49
347
7
32
Order By: Relevance
“…Around 5% of patients presenting with an ACS exhibit normal coronary angiograms, a proportion that is higher in young patients (8,32). Various mechanisms have been hypothesized, such as coronary spasm, and acquired or inherited coagulation disorders (9,33).…”
Section: Discussionmentioning
confidence: 99%
“…Around 5% of patients presenting with an ACS exhibit normal coronary angiograms, a proportion that is higher in young patients (8,32). Various mechanisms have been hypothesized, such as coronary spasm, and acquired or inherited coagulation disorders (9,33).…”
Section: Discussionmentioning
confidence: 99%
“…The relatively high prevalence of acute myocardial infarction associated with normal coronary angiography was described in young patients (younger than 40 years of age) (17,18). Zimmerman et al (18) studied the angiographic characteristics, coronary risk factors and prognoses in young women and men with a history of myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Zimmerman et al (18) studied the angiographic characteristics, coronary risk factors and prognoses in young women and men with a history of myocardial infarction. These authors reported normal coronary angiography, or nonobstructive disease, in 34% of young women and 22% of young men.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of vulnerable plaque established in the general population clearly requires verification in regard to young and very young patients. In the 1988 study by Wolfe and Vacek [13], comparing angiographic characteristics of the coronary arteries in patients with MI aged ≤ 35 years vs. ≥ 55 years, a nearly complete coronary occlusion was found in all young patients with an abnormal coronary angiogram. Although that study included only 35 patients ≤ 35 years, this finding was highlighted by the authors and is consistent with our study findings.…”
Section: Discussionmentioning
confidence: 99%